Pengembangan Media Komik “KOKO” Berbasis Karakter untuk Meningkatkan Hasil Belajar Mata Pelajaran Matematika di Sekolah Dasar - Aini, Alifa Feby Nur; Widayanti, Aning; Farisia, Hernik (Universitas Negeri Surabaya, 2024)
Character-based koko comic media is an innovation in developing learning media, especially for mathematics subjects of grade 3 fractional material at MI NU Wedoro Sidoarjo. The purpose of this research aims to determine the level of validity, practicality, and effectiveness of cocoa comic media. In this study, researchers used Research and Development (R&D) research methods with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data obtained through observation and interviews, validation instruments, questionnaires and tests. Information or data that has been obtained is then analyzed and produces conclusions from teachers, students, material experts, media experts as a repsondent in providing information on this development research. The results showed that the level of validity of comic media is in the category of very valid and can be used with a little revision. In addition, for the level of practicality of comic media, koko is in the very practical category. Data on the effectiveness of comics is also in the category of very effective, because it sees an increase in student learning outcomes from post-test and pre-test. Keywords: Mathematics, Comics Media, Learning, Development.